واقع التخطيط الاستراتيجي التشاركي في البلديات الفلسطينية : دراسة ميدانية - الشنتف، يوسف أحمد سعيد Alshantaf, Yousuf Ahmed Said (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2015)
يهدف البحث للتعرف على واقع تطبيق التخطيط الاستراتيجي التشاركي في البلديات الفلسطينية؛ وقد استخدم الباحث المنهج الوصفي التحليلي لهذا الغرض، وقد تكون مجتمع البحث من (أعضاء المجلس البلدي، وموظفي البلدية، والعملاء) المشاركين في عملية التخطيط الاستراتيجي التشاركي في البلديات الفلسطينية محل الدراسة (بلدية غزة، بلدية دير البلح، بلدية المغازي، بلدية البريج)، والبالغ عددهم (347) مفردة. وتوصلت الدراسة لوجود موافقة مرتفعة من عينة البحث حول مستوى تطبيق البلديات الفلسطينية للتخطيط الاستراتيجي التشاركي. كما أوصت الدراسة بضرورة تعزيز مفهوم الشراكة مع (المؤسسات والوزارات ذات العلاقة) بما يحقق التكامل بين خطة البلدية وخطط المؤسسات والوزارات ذات العلاقة، بالإضافة للعمل على ترسيخ مفهوم التخطيط الاستراتيجي التشاركي في البلديات الفلسطينية.
The research aims to determine the role of Participatory Strategic Planning (PSP) in improving the services quality of the Palestinian Municipalities. The researcher used descriptive analytical approach to achieve the aim of the research. The population consists of the participants in the process of the (PSP) (municipal council members, municipality employees and customers) at the following municipalities (Gaza, Dir Al Balah, El Maghazi and El Bureij), and the population of the research was consisted of (347) elements. The research found a statistical significant difference among the responses of the participants in the process of (PSP) that are related to the level of the (PSP), for the municipal council members. In the light of these results the study recommended to enhancing the conception of partnership with the concerned ministries and institutions to achieve integration between the municipality plan and the plans of the concerned ministries and institutions
Keywords: البلديات -- التخطيط الاستراتيجي التشاركي -- المجتمع الفلسطيني